Implementation of Digital Marketing in Increasing Marketing Distribution at Pt. Sreeya Sewu Indonesia, Tbk - Anggraeni, Gita Siwi (Yayasan Gema Bina Nusantara, 2024)
The goal of this research is to shed light on the marketing process at PT. Sreeya Sewu Indonesia, Tbk, with a focus on enhancing its digital marketing distribution. The data collection process for this company starts from December 11, 2023, to January 5, 2024. After the data collection process is complete, the researcher carries out transcription and data processing until January 19, 2024. This research employs a descriptive-qualitative approach. Data collection uses observation, interviews, field notes, and documentation. The results revealed that the decline in the previous quarter was caused by a slow distribution process, which was exacerbated by the difficulty in obtaining raw materials due to soaring prices, and a current lack of intensity in digital marketing, particularly in social media and email.